Auditory Brain Stem Responses in the C57BL/6J Fragile X Syndrome-Knockout Mouse Model - Chawla, Amita; McCullagh, Elizabeth A. (Frontiers in Integrative Neuroscience, 2022)
Sensory hypersensitivity, especially in the auditory system, is a common symptom in Fragile X syndrome (FXS), the most common monogenic form of intellectual disability. However, linking phenotypes across genetic background strains of mouse models has been a challenge and could underly some of the issues with translatability of drug studies to the human condition. This study is the first to characterize the auditory brain stem response (ABR), a minimally invasive physiological readout of early auditory processing that is also used in humans, in a commonly used mouse background strain model of FXS, C57BL/6J. We measured morphological features of pinna and head and used ABR to measure the hearing range, and monaural and binaural auditory responses in hemizygous males, homozygous females, and heterozygous females compared with those in wild-type mice. Consistent with previous study, we showed no difference in morphological parameters across genotypes or sexes. There was no significant difference in hearing range between the sexes or genotypes, however there was a trend towards high frequency hearing loss in male FXS mice. In contrast, female mice with homozygous FXS had a decreased amplitude of wave IV of the monaural ABR, while there was no difference in males for amplitudes and no change in latency of ABR waveforms across sexes and genotypes. Finally, males with FXS had an increased latency of the binaural interaction component (BIC) at 0 interaural timing difference compared with that in wild-type males. These findings further clarify auditory brain stem processing in FXS by adding more information across genetic background strains allowing for a better understanding of shared phenotypes.